BAHASA INGGRIS DI MASA PANDEMI: KENDALA PEMBELAJARAN DI SDN AENGDAKE I - Akhmad Feri Fatoni; Tita Tanjungsari; Emdat Suprayitno (JURNAL PENDIDIKAN DASAR, 2021)
Abstract: The Covid-19 pandemic that has hit the world requires the education process to be carried out innovatively, including the education process in Indonesia. At the elementary school level, the use of online learning is recommended by using a platform with a simple operating system such as WhatssApp. The application of online learning requires the readiness of various parties, both from schools, office holders, students, and parents.This research was conducted in grade IV of SDN Aengdake I using qualitative research methods (case studies). This study aimed to describe the obstacles or difficulties faced by teachers and students in learning English online at SDN Aengdake I. In general, there were two factors that underlie the obstacles in learning English online at SDN Aengdake I, they were management and technical factors. In terms of management factors, teachers had difficulty using innovative teaching methods, limited teaching time, and many students lack of discipline in learning process. In technical factor, the economic condition of the family affected the success of online teaching and learning. Keywords: Difficulties of online learning, English learning, Grade IV students of SDN Aengdake I